Cellulose an ageless renewable green nanomaterial for medical applications: an overview of ionic liquids in extraction, separation and dissolution of cellulose - Bhat, A. H. (2019)
Cellulose is a renewable natural fiber, which has gained enormous and significant research interest and evolved as the prime and promising candidate for replacing synthetic fibers. The various sources of cellulose, which is one of the world's most ubiquitous and renewable biopolymer resources, include trees, plants, tunicate and bacteria. The renewable biomaterial in the form of nanocellulose and its composites have been included in this review having the broad range of medical applications, viz.; tissue engineering, cardiovascular surgery, dental, pharmaceuticals, veterinary, adhesion barriers and skin therapy. These grafts are being fabricated from biodegradable materials. Bacterial cellulose is also an emerging renewable biomaterial with immense potential in biomedical field. The fabrication methods, characteristic properties and various overwhelming applications of cellulosic composites are explicitly elucidated in this review. The crux of this review is to exhibit the latest state of art, development in the field of cellulosic nanocomposite science and technology research and their applications towards biomedical field. Among the fourteen principle of green chemistry the two key principles i.e. using environmentally preferable solvents and bio-renewable feed-stocks covers in dissolution of cellulose in ionic liquids (ILs). In addition, this review covers about the comprehensive extraction and dissolution of cellulose and nanocellulose using ILs.